Da Genova a Detroit a Pechino. Geografie economiche della globalizzazione - Francesco Dini (Bollettino della Società Geografica Italiana)
China is an exceptional space under many aspects and proposes very thorny problems about current conditions of globalization, markets and capitalism. In the large literature on China of the last decades a particular space is occupied by Giovanni Arrighi and his Systemic Cycles of Accumulation, an organic theory of capitalism, but also a theory of hegemonic transitions. Arrighi presented this theory in his work The Long Twentieth Century (1994), which discussed the exhaustion of the US systemic cycle, but did not identify China as the emerging power. This would happen only thirteen years later, with his other work Adam Smith in Beijing. The article discusses this strange case of presbyopia, curious if we consider the conceptual depth and analytical accuracy of Arrighi. Moreover, starting from the Chinese case, it discusses the theory of Systemic Cycles of Accumulation, as it can contribute to a geographical reading of contemporary world economy and politics.